PENGARUH AKTIVITAS BELAJAR TERHADAP PERFORMANSI BELAJAR EKONOMI SISWA KELAS XI IPS SMA NEGERI 03 PONTIANAK - Aula Yuli Mukarromah; Endang Purwaningsih; Achmadi Achmadi (Universitas Tanjungpura, 2021)
AbstractThe form of this research is quantitative research with ex post facto research type. Thesample in this study were students of class XI IPSat SMA Negeri 03 Pontianak, totaling 94students. The sampling method is probability sampling. The results of this study indicatethat after conducting a simple linear regression test on the two variabels it is said thatlearning activity has a positive effect on he learning performance of students with theregression equation Y = 25.829 + 0,714 X and has an effect of 54%. By conducting ahypothesis test comparing the significance value with 0.05 so that the significance value isobtained of 0.001 <0.05, so it can be concluded that (Ho) is rejected and (Ha) is accepted.Continue to test the hypothesis comparing the t value with the t table obtained by t count of8.529 > 1.999 t table so that it is concluded that Ho) is rejected and (Ha) is accepted,which means that there is an influence between